Degradation of Toxic Dye and Antimicrobial and Free Radical Potential of Environmental Benign Zinc Oxide Nanoparticles. (19th July 2022) - Rajeshkumar, Shanmugam; Santhoshkumar, Jayakodí; Parameswari, R. P.; Saravanan, S.; Balusamy, Sri Renukadevi; Arunachalam, Kalirajan
Abstract : Several industries have become major contributors to waterbody contamination due to the improper removal of dyes and effluents into water bodies. Due to their carcinogenic properties and low biodegradability, dye degradation is a considerable danger to people, animals, and the oceanic environment. As part of this study, Andrographis paniculata leaf extract was used as a reducing and stabilizing agent to synthesize zinc nanoparticles and degrade dyes such as methyl red and eosin. Zinc oxide nanoparticles (ZnONPs) showed a surface plasmon resonance peak at 430 nm in the UV spectrum. The FTIR result showed a band at 597.93 cm −1 that confirmed the formation of zinc nanoparticles. AFM results revealed spherical ZnONPs. The SEM results predicted an average particle size of 60 nm for crystalline particles. Biologically synthesized zinc nanoparticles exhibited greater antibacterial activity against Pseudomonas spp. and Proteus spp. but lesser activity against Klebsiella spp. and S. aureus . At 1000  μ g/ml concentration, ZnONPs had the highest antioxidant activity of 45.34%. An ultraviolet-visible spectrophotometer measured dye degradation progress between 300 and 800 nm. For methyl red, the maximum absorption peak was measured at 415 nm, and for eosin, the maximum peak value was measured between 500 and 515 nm.